Correlations between renal function and the total kidney volume measured on imaging for autosomal dominant polycystic kidney disease: A systematic review and meta-analysis. Issue 95 (October 2017) - Jo, Woo Ri; Kim, Seong Hee; Kim, Kyung Won; Suh, Chong Hyun; Kim, Jeong Kon; Kim, Hyosang; Lee, Jong Gu; Oh, Woo Yong; Choi, Seong Eun; Pyo, Junhee
Abstract: Purpose: To provide a systematic summary of total kidney volume (TKV) as an imaging biomarker in clinical trials for autosomal dominant polycystic kidney disease (ADPKD), focusing on the correlation between TKV and renal function. Methods: A computerized literature search was performed using MEDLINE and EMBASE databases for studies that evaluated the correlation between TKV and the glomerular filtration rate (GFR) and between the TKV growth rate and GFR decline rate. A meta-analysis was performed to generate the summary correlation coefficient ( r ). A qualitative review was performed to evaluate the characteristics of TKV as an imaging biomarker. Results: Eighteen articles including a total sample size of 2835 patients were retrieved. Meta-analysis revealed substantial correlations between TKV and GFR [ r, −0.520; 95% confidence interval (CI), −0.60 to −0.43] and between the TKV growth rate and GFR decline rate [ r, −0.320; 95% CI, −0.54 to −0.10]. The quantitative review revealed that baseline TKV can affect the TKV growth rate and GFR decline rate, such that patients with a higher baseline TKV showed faster TKV growth and GFR decline. There was significant variability in image acquisition and analysis methods. Conclusion: There were significant negative correlations between TKV and GFR as well as between TKV growth and GFR decline rates, suggesting that TKV imaging is a useful biomarker in clinical trials. However, standardization—or at least trial-specific standardization—of image acquisition and analysis techniques is required to use TKV as a reliable biomarker.